Organic alkali-activated geopolymer condensate as well as preparation method and application thereof

By adding organic alkali in the preparation process of the ground polymer cured product, adjusting the modulus of the water glass and delaying the hydration reaction, the problem of 'frost' phenomenon in the ground polymer cured product is solved, and the compressive strength performance is significantly improved , broadened the application areas.

CN119430750AActive Publication Date: 2025-02-14CHINA NAT PETROLEUM CORP +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411335416.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-02-14
Estimated Expiration
2044-09-24

AI Technical Summary

Technical Problem

The solidified earth polymers are prone to 'frost' during use, resulting in a decrease in mechanical strength and stability, and the prior art is difficult to effectively solve this problem.

Method used

By adding organic alkali to prepare the ground polymer cured product, adjusting the modulus of the water glass, delaying the hydration reaction, prolonging the settling time, and avoiding drying and cracking, thereby forming a ground polymer with low porosity and high density.

Benefits of technology

It effectively avoids the occurrence of 'frost' phenomenon, significantly improves the compressive strength performance of the polymer cured substances activated by organic alkalis, and broadens its application areas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430750A_ABST
    Figure CN119430750A_ABST
Patent Text Reader

Abstract

The invention discloses an organic alkali-activated geopolymer condensate as well as a preparation method and application thereof, and the method comprises the following steps: adding water glass, a surfactant and a defoaming agent into water, heating and uniformly stirring to obtain a micelle solution, and cooling to room temperature for later use; wherein the water glass accounts for 10-40.33% of the weight of the water, the surfactant accounts for 1-7.14% of the weight of the water, and the defoaming agent accounts for 0.17-1% of the weight of the water; adding organic alkali into the micelle solution, and uniformly mixing to obtain a mixed solution; wherein the organic base accounts for 1.83-11.67% of the weight of the water; weighing fly ash according to a water-to-fly ash water-to-water ratio of 0.3-0.35, pouring the fly ash into a stirring pot of a cement mortar stirrer, pouring the mixed solution into the stirring pot, and stirring and mixing to prepare the organic alkali-activated geopolymer condensate. The phenomenon of scumming is avoided, meanwhile, the compressive strength performance of the organic alkali-activated geopolymer condensate is remarkably improved, and the organic alkali-activated geopolymer condensate has very important practical significance for widening the application field of the geopolymer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of geopolymer-based materials, and in particular to an organic base-activated geopolymer solidified material, a preparation method and application thereof. Background Art

[0002] Geopolymer is a kind of gel material with a three-dimensional network inorganic polymer structure formed by silicon-oxygen tetrahedron and aluminum-oxygen tetrahedron. It was first developed by Professor Davidovits of France in the late 1970s. The structure is between quasi-crystalline and amorphous. It does not have a specific chemical formula and is usually expressed by the chemical formula M x [-(Si-O2) z -Al-O] n ·ωH2O, where M is an alkali metal cation, z is the Si / Al molar ratio in the structure, n is the degree of polymerization, and ω is the number of chemically bound water. Because this type of material has this special network-like polymerization structure, it has stable physical and chemical properties, high strength, high temperature resistance, acid and alkali corrosion resistance and other excellent properties. It has a wide range of applications in fire protection and heat insulation, construction, heavy metal solidification, and nuclear waste consolidation.

[0003] The most common method for preparing geopolymers is to use alkaline solution to stimulate them. However, since this method uses a high concentration of alkaline solution to dissolve the raw materials during the preparation process, there will inevitably be excess alkaline substances remaining after the solid raw materials are mixed with the alkaline activator solution and the geopolymerization reaction occurs. Summary of the invention

[0004] In order to eliminate the "frosting" phenomenon of geopolymer solidified materials during use, thereby improving the mechanical strength and stability of geopolymer solidified materials, and at the same time enriching technical routes and increasing selection space, an organic base-activated geopolymer solidified material, a preparation method and its application are provided in the embodiments of the present invention.

[0005] In a first aspect, an embodiment of the present invention provides a method for preparing an organic base-activated geopolymer solidified material, which may include:

[0006] Add water glass, surfactant and defoamer into water, heat and stir to obtain micellar solution, and then cool to room temperature for use; wherein the weight percentage of water glass to water is 10-40.33%, the weight percentage of surfactant to water is 1-7.14%, and the weight percentage of defoamer to water is 0.17-1%;

[0007] Adding an organic base to the micellar solution and mixing them uniformly to obtain a mixed solution; wherein the weight percentage of the organic base to the water is 1.83-11.67%;

[0008] The fly ash is weighed according to the water-to-fly ash water-binder ratio of 0.3-0.35, poured into a mixing pot of a cement mortar mixer, and the mixed solution is poured into the mixing pot and stirred to prepare an organic alkali-activated geopolymer solidified product.

[0009] In one embodiment, the weight percentage of the water glass to the water is 34.57-40.33%, the weight percentage of the surfactant to the water is 1-2%, the weight percentage of the defoaming agent to the water is 0.29-1%; the weight percentage of the organic base to the water is 3-11.42% or 11.67-20%.

[0010] In another embodiment, the weight percentage of the surfactant to the water is 1.71-2%, the weight percentage of the defoamer to the water is 0.29-0.5%; and the weight percentage of the organic base to the water is 8.57-10%.

[0011] In another embodiment, the surfactant is at least one of the following: lignin sulfonates, naphthalenes, melamines, aminosulfonates, fatty acids, and polycarboxylates.

[0012] In another embodiment, the defoaming agent is at least one of the following: oils, alcohols, synthetic fatty acids and fatty acid esters, amides, phosphates, organosilicon compounds, halogenated organics, polyethers and polyether-type nonionic surfactants.

[0013] In another embodiment, the organic base is an amine compound, including at least one of the following: aliphatic amines, alcohol amines, amides, alicyclic amines, aromatic amines, and naphthyl amines.

[0014] In another embodiment, the modulus of the water glass is 3.3.

[0015] In a second aspect, an embodiment of the present invention provides an organic base-activated geopolymer solidified material prepared according to the method for preparing an organic base-activated geopolymer solidified material according to the first aspect.

[0016] In a third aspect, an embodiment of the present invention provides an application of an organic base-activated geopolymer solidified material prepared by the method for preparing an organic base-activated geopolymer solidified material according to the first aspect in a construction project.

[0017] In a fourth aspect, an embodiment of the present invention provides a use of an organic base-activated geopolymer solidified material prepared by the method for preparing an organic base-activated geopolymer solidified material according to the first aspect in well completion or cementing.

[0018] The beneficial effects of the above technical solution provided by the embodiment of the present invention include at least:

[0019] The embodiment of the present invention provides an organic alkali-activated geopolymer solidified material, a preparation method and an application thereof. The organic alkali-activated geopolymer solidified material prepared by the preparation method has a synergistic effect between the various components of the geopolymer further enhanced. By adding an organic alkali, the modulus of water glass is adjusted, the early hydration reaction is delayed, the early coagulation time is extended, and the shrinkage and cracking phenomena are avoided, thereby forming a geopolymer with low porosity and high density. This not only avoids the occurrence of the "frosting" phenomenon, but also significantly improves the compressive strength performance of the organic alkali-activated geopolymer solidified material, which has a very important practical significance for broadening the application field of the geopolymer.

[0020] Other features and advantages of the present invention will be described in the following description, and partly become apparent from the description, or understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained by the structures particularly pointed out in the written description and the accompanying drawings.

[0021] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:

[0023] Figure 1 The present invention provides a flowchart of a method for preparing an organic base-activated geopolymer solidified material according to an embodiment of the present invention. DETAILED DESCRIPTION

[0024] The exemplary embodiments of the present disclosure will be described in more detail below with reference to the accompanying drawings. Although the exemplary embodiments of the present disclosure are shown in the accompanying drawings, it should be understood that the present disclosure can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided to enable a more thorough understanding of the present disclosure and to fully convey the scope of the present disclosure to those skilled in the art.

[0025] The inventors have discovered that during the later use of geopolymers, residual alkali metal ions will gradually transfer to the surface along with the internal pores and crystallize to form a white frosty substance, commonly known as "flouring". The occurrence of this phenomenon will affect the later performance of the geopolymer, causing the gel structure to become loose and porous, thereby causing the performance of the sample to decrease. Therefore, developing a preparation method that can eliminate the frosting phenomenon of geopolymers and make them have good mechanical strength and stability is of great practical significance for broadening the application field of geopolymers. In view of the above problems, the present invention is proposed to provide an organic alkali-activated geopolymer solid, a preparation method and its application that overcome the above problems or at least partially solve the above problems.

[0026] The present invention provides a method for preparing a solidified geopolymer excited by an organic base, Figure 1 As shown, the method may include the following steps:

[0027] Step S11, adding water glass, surfactant and defoaming agent into water, heating and stirring to obtain a micellar solution, and then cooling to room temperature for use; wherein the weight percentage of water glass to water is 10-40.33%, the weight percentage of surfactant to water is 1-7.14%, and the weight percentage of defoaming agent to water is 0.17-1%.

[0028] In this step, water glass is added to water to make the water dissolve the water glass; the surfactant is at least one of the following: lignin sulfonates, naphthalene, melamine, aminosulfonates, fatty acids, polycarboxylates, and the surfactant is added to make the fly ash and water mix more evenly; the defoamer is at least one of the following: oils and fats, alcohols, synthetic fatty acids and fatty acid esters, amides, phosphates, organosilicon compounds, halogenated organics, polyethers and polyether-type nonionic surfactants, and the defoamer is added to reduce the foaming amount of the surfactant during stirring and dissolving.

[0029] Step S12, adding an organic base to the micellar solution and mixing them evenly to obtain a mixed solution; wherein the weight percentage of the organic base to water is 1.83-11.67%.

[0030] It should be noted that in this step, the organic base is an amine compound, including at least one of the following: aliphatic amines, alcohol amines, amides, alicyclic amines, aromatic amines, and naphthyl amines. In the embodiment of the present invention, the preferred organic base is one of aliphatic amines, alcohol amines, and aromatic amines, and its main function is to provide OH- to the system and increase the pH value of the system. After adding the organic base, since the organic base has a certain volatility, in order to prevent the pH value from changing greatly in the embodiment of the present invention, it is necessary to mix and place in a sealed state.

[0031] Step S13, weighing fly ash according to a water-to-fly ash water-binder ratio of 0.3-0.35, pouring the fly ash into a mixing pot of a cement mortar mixer, pouring the mixed solution into the mixing pot and stirring to prepare an organic alkali-activated geopolymer solidified product.

[0032] The method for preparing the organic base-activated geopolymer solidified material provided in the embodiment of the present invention further enhances the synergistic effect between the various components of the geopolymer. By adding the organic base, the modulus of the water glass is adjusted, the early hydration reaction is delayed, the early setting time is extended, and the shrinkage and cracking phenomena are avoided, thereby forming a geopolymer with low porosity and high density. This not only avoids the occurrence of the "frosting" phenomenon, but also significantly improves the compressive strength performance of the organic base-activated geopolymer solidified material, which has a very important practical significance for broadening the application field of the geopolymer.

[0033] In a preferred embodiment, the weight percentage of the water glass to the water is 34.57-40.33%, the weight percentage of the surfactant to the water is 1-2%, the weight percentage of the defoaming agent to the water is 0.29-1%; the weight percentage of the organic base to the water is 3-11.42% or 11.67-20%.

[0034] In the embodiment of the present invention, the synergistic effect between the components is enhanced by adjusting the components of the geopolymer. Under the premise of not affecting the mechanical strength and stability, not only the "frosting" phenomenon is avoided, but also the compressive strength performance of the organic alkali-activated geopolymer solidified material is significantly improved.

[0035] In another more preferred embodiment, the weight percentage of the surfactant to the water is 1.71-2%, the weight percentage of the defoamer to the water is 0.29-0.5%; and the weight percentage of the organic base to the water is 8.57-10%.

[0036] The synergistic effect between the various components of the geopolymer in the embodiment of the present invention is further enhanced. By adding an organic base, the modulus of water glass is adjusted, the early hydration reaction is delayed, the early setting time is extended, and shrinkage and cracking are avoided, thereby forming a geopolymer with low porosity and high density. This not only avoids the occurrence of the "frosting" phenomenon, but also significantly improves the compressive strength of the organic base-activated geopolymer solidified material, which has a very important practical significance for broadening the application field of the geopolymer.

[0037] Based on the above preparation method, the following examples and comparative examples are provided in the present invention to verify the "flourishing" phenomenon and compressive strength effect of the organic base-activated geopolymer solidified material prepared in the present invention as follows:

[0038] The water glass used in the following Examples 1 to 6 of the present invention and Comparative Examples 1 to 6 is also called powdered instant sodium silicate, with a modulus of 3.3 and a structural formula of (NaOH) x (Na2SiO3) y · zH2O, CAS No. 13870-30-9, the mass ratio of each component is as follows: SiO2 content is 58.32%, Na2O content is 20.74%. The commercial sources of some raw materials and reagents in the examples of the present invention are as follows:

[0039] Raw material name Commercial Sources Polyether modified silicone oil Qingdao Meiside Silicone Co., Ltd. Polysiloxane DC-200 Jiangsu Bosite Chemical Technology Co., Ltd. Polyethylene glycol 200 Shanghai Aladdin Biochemical Technology Co., Ltd. n-Octanol Shanghai Aladdin Biochemical Technology Co., Ltd. 2-Naphthalenesulfonic acid Shanghai Aladdin Biochemical Technology Co., Ltd.

[0040] It should also be noted that other reagent raw materials involved in the examples and comparative examples of the present invention are all commercially available general reagent products.

[0041] Example 1

[0042] In this embodiment, the organic base-activated geopolymer solidified material is prepared from fly ash, water glass (modulus 3.3), sodium lignin sulfonate, polydimethylsiloxane, and diethylenetriamine.

[0043] Weigh 121g of water glass, add it to 300g of water, then add 6g of sodium lignin sulfonate and 1.5g of polydimethylsiloxane, heat to 60°C, stir evenly to obtain a micellar solution, and cool to room temperature for use; add 30g of diethylenetriamine to the above micellar solution, stir for 30min to obtain a uniform mixed solution, seal and place for 24 hours before use.

[0044] According to the water-cement ratio of 0.3, weigh 1 kg of fly ash, pour it into the mixing pot of the cement mortar mixer, add the above mixed solution, stir slowly for 2 minutes, then stir quickly for 2 minutes, and put it into the triple mold. Fix the triple mold on the vibration table and vibrate the material. Cover it with plastic wrap and place it in a constant temperature and humidity curing box for curing, with a humidity of 90% and a temperature of 30 degrees. The curing time is 7d, 14d, 28d, 56d, and 63d. Take out the samples separately to observe whether there is "frosting" phenomenon, and test its compressive strength.

[0045] As a control group of Example 1, Comparative Example 1 completed the following test:

[0046] Weigh 121g of water glass, add it to 300g of water, then add 6g of sodium lignin sulfonate and 1.5g of polydimethylsiloxane, heat to 60°C, stir evenly to obtain a micellar solution, and cool to room temperature for use; add 23.3g of NaOH to the above solution, stir for 30 minutes to obtain a uniform mixed solution, seal and place for 24 hours before use.

[0047] Weigh 1 kg of fly ash, pour it into the mixing pot of the cement mortar mixer, add the above mixed solution, stir slowly for 2 minutes, then stir quickly for 2 minutes, and put it into the triple mold. Fix the triple mold on the vibration table and vibrate the material. Cover it with plastic wrap and place it in a constant temperature and humidity curing box for curing, with a humidity of 90% and a temperature of 30 degrees. The curing time is 7d, 14d, 28d, 56d, and 63d. Take out the samples separately to observe whether there is "frosting" phenomenon, and test its compressive strength.

[0048] Table 1 Verification results of the "flour" phenomenon and compressive strength of the solidified material prepared in Example 1

[0049] Maintenance time / day Is there a "frosting" phenomenon? Compressive strength / MPa 7 none 5.3 14 none 17.6 28 none 25.3 56 none 37.2 63 none 40.3

[0050] Table 2 Verification results of the "flour" phenomenon and compressive strength of the solidified material prepared in Comparative Example 1

[0051] Maintenance time / day Is there a "frosting" phenomenon? Compressive strength / MPa 7 none 5.5 14 Appear 16.9 28 have 23.1 56 have 33.3 63 have 35.6

[0052] Example 2

[0053] In this embodiment, the organic base-activated geopolymer solidified material is prepared from fly ash, water glass (modulus 3.3), OP-15 (alkylphenol polyoxyethylene (15) ether, or alkylphenol polyoxyethylene ether-15), polyether-modified silicone oil, and acetanilide.

[0054] Weigh 100g of water glass, add it to 350g of water, then add 25g of OP-15 and 3.5g of polyether-modified silicone oil, heat to 60°C, stir evenly to obtain a micellar solution, and cool to room temperature for use; add 70g of acetanilide to the above micellar solution, stir for 30 minutes to obtain a uniform mixed solution, and leave it for 24 hours for use.

[0055] According to the water-cement ratio of 0.35, weigh 1 kg of fly ash, pour it into the mixing pot of the cement mortar mixer, add the above solution, stir slowly for 2 minutes, then stir quickly for 2 minutes, and put it into the triple mold. Fix the triple mold on the vibration table and vibrate the material. Cover it with plastic wrap and place it in a constant temperature and humidity curing box for curing, with a humidity of 90% and a temperature of 30 degrees. The curing time is 7d, 14d, 28d, 56d, and 63d. Take out the samples separately to observe whether there is "frosting" phenomenon, and test its compressive strength.

[0056] As a control group of Example 2, Comparative Example 2 completed the following test:

[0057] Weigh 150g of water glass, add it to 350g of water, then add 15g of OP-15 and 1.5g of polyether-modified silicone oil, heat to 60°C, stir evenly to obtain a micellar solution, and cool to room temperature for use; add 25g of NaOH to the above micellar solution, stir for 30 minutes to obtain a uniform mixed solution, and leave it for 24 hours for use.

[0058] Weigh 1 kg of fly ash, pour it into the mixing pot of the cement mortar mixer, add the above mixed solution, stir slowly for 2 minutes, then stir quickly for 2 minutes, and put it into the triple mold. Fix the triple mold on the vibration table and vibrate the material. Cover it with plastic wrap and place it in a constant temperature and humidity curing box for curing, with a humidity of 90% and a temperature of 30 degrees. The curing time is 7d, 14d, 28d, 56d, and 63d. Take out the samples respectively to observe whether there is "frosting" phenomenon, and test its strength.

[0059] Table 3 Verification results of the "flour" phenomenon and compressive strength of the solidified material prepared in Example 2

[0060]

[0061]

[0062] Table 4 Verification results of the "flour" phenomenon and compressive strength of the solidified material prepared in Comparative Example 2

[0063] Maintenance time / day Is there a "frosting" phenomenon? Compressive strength / MPa 7 none 5.9 14 none 16.7 28 Appear 24.9 56 have 30.3 63 have 33.6

[0064] Embodiment 3:

[0065] In this embodiment, the organic base-activated geopolymer solidified material is prepared from fly ash, water glass (modulus 3.3), Span-80, polysiloxane, and guanidine.

[0066] Weigh 30g of water glass and add it to 300g of water, then add 3g of Span-80 (sorbitan monooleate, Span 80, CAS No.: 1338-43-8; molecular formula: C 24 H 44 O6) and 1.5g polysiloxane, heat to 60°C, stir evenly to obtain a micellar solution, and cool to room temperature for use; add 9g guanidine to the above micellar solution, stir for 30 minutes to obtain a uniform mixed solution, and leave it for 24 hours for use.

[0067] According to the water-cement ratio of 0.30, weigh 1 kg of fly ash, pour it into the mixing pot of the cement mortar mixer, add the above mixed solution, stir slowly for 2 minutes, then stir quickly for 2 minutes, and put it into the triple mold. Fix the triple mold on the vibration table and vibrate the material. Cover it with plastic wrap and place it in a constant temperature and humidity curing box for curing, with a humidity of 90% and a temperature of 30 degrees. The curing time is 7d, 14d, 28d, 56d, and 63d. Take out the samples respectively to observe whether there is "frosting" phenomenon, and test its strength. And test its strength.

[0068] As a control group of Example 3, Comparative Example 3 completed the following test:

[0069] Weigh 30g of water glass, add it to 300g of water, then add 3g of Span-80 and 1.5g of polysiloxane, heat to 60°C, stir evenly to obtain a micellar solution, and cool to room temperature for use; add 5.5g of NaOH to the above micellar solution, stir for 30 minutes to obtain a uniform mixed solution, and leave it for 24 hours for use.

[0070] Weigh 1 kg of fly ash, pour it into the mixing pot of the cement mortar mixer, add the above mixed solution, stir slowly for 2 minutes, then stir quickly for 2 minutes, and put it into the triple mold. Fix the triple mold on the vibration table and vibrate the material. Cover it with plastic wrap and place it in a constant temperature and humidity curing box for curing, with a humidity of 90% and a temperature of 30 degrees. The curing time is 7d, 14d, 28d, 56d, and 63d. Take out the samples respectively to observe whether there is "frosting" phenomenon, and test its strength.

[0071] Table 5 Verification results of the "flour" phenomenon and compressive strength of the solidified material prepared in Example 3

[0072] Maintenance time / day Is there a "frosting" phenomenon? Compressive strength / MPa 7 none 4.1 14 none 22.3 28 none 35.9 56 none 40.9 63 none 40.9

[0073] Table 6 Verification results of the "flour" phenomenon and compressive strength of the solidified material prepared in Comparative Example 3

[0074] Maintenance time / day Is there a "frosting" phenomenon? Compressive strength / MPa 7 none 5.0 14 none 17.6 28 Appear 21.9 56 have 27.3 63 have 33.6

[0075] Embodiment 4:

[0076] In this embodiment, the organic base-activated geopolymer solidified material is prepared from fly ash, water glass (modulus 3.3), calcium lignin sulfonate, polyethylene glycol, and tetraethylene pentamine.

[0077] Weigh 121g of water glass, add it to 350g of water, then add 6g of calcium lignin sulfonate and 1g of polyethylene glycol, heat to 60°C, stir evenly to obtain a micellar solution, and cool to room temperature for use; add 30g of tetraethylene pentamine to the above micellar solution, stir for 30 minutes to obtain a uniform mixed solution, and leave it for 24 hours for use.

[0078] According to the water-cement ratio of 0.35, weigh 1 kg of fly ash, pour it into the mixing pot of the cement mortar mixer, add the above mixed solution, stir slowly for 2 minutes, then stir quickly for 2 minutes, and put it into the triple mold. Fix the triple mold on the vibration table and vibrate the material. Cover it with plastic wrap and place it in a constant temperature and humidity curing box for curing, with a humidity of 90% and a temperature of 30 degrees. The curing time is 7d, 14d, 28d, 56d, and 63d. Take out the samples respectively to observe whether there is "frosting" phenomenon, and test its strength. And test its strength.

[0079] As a control group of Example 4, Comparative Example 4 completed the following test:

[0080] Weigh 121g of water glass, add it to 350g of water, then add 6g of calcium lignin sulfonate and 1g of polyethylene glycol, heat to 60°C, stir evenly to obtain a micellar solution, and cool to room temperature for use; add 23g of NaOH to the above micellar solution, stir for 30 minutes to obtain a uniform mixed solution, and leave it for 24 hours for use.

[0081] Weigh 1 kg of fly ash, pour it into the mixing pot of the cement mortar mixer, add the above mixed solution, stir slowly for 2 minutes, then stir quickly for 2 minutes, and put it into the triple mold. Fix the triple mold on the vibration table and vibrate the material. Cover it with plastic wrap and place it in a constant temperature and humidity curing box for curing, with a humidity of 90% and a temperature of 30 degrees. The curing time is 7d, 14d, 28d, 56d, and 63d. Take out the samples respectively to observe whether there is "frosting" phenomenon, and test its strength.

[0082] Table 7 Verification results of "flourish" phenomenon and compressive strength of the solidified material prepared in Example 4

[0083] Maintenance time / day Is there a "frosting" phenomenon? Compressive strength / MPa 7 none 5.5 14 none 18.2 28 none 27 56 none 40 63 none 40.7

[0084] Table 8 Verification results of the "flour" phenomenon and compressive strength of the solidified material prepared in Comparative Example 4

[0085]

[0086]

[0087] Embodiment 5:

[0088] In this embodiment, the organic base-activated geopolymer solidified material is prepared from fly ash, water glass (modulus 3.3), tetramethylacetyloctahydronaphthalene, isooctyl phosphate, and triethanolamine.

[0089] Weigh 95g of water glass, add it to 300g of water, then add 7g of tetramethylacetyl octahydrogen and 0.5g of isooctyl phosphate, heat to 60°C, stir evenly to obtain a micellar solution, and cool to room temperature for use; add 35g of triethanolamine to the above micellar solution, stir for 30 minutes to obtain a uniform mixed solution, and leave it for 24 hours for use.

[0090] According to the water-cement ratio of 0.30, weigh 1 kg of fly ash, pour it into the mixing pot of the cement mortar mixer, add the above mixed solution, stir slowly for 2 minutes, then stir quickly for 2 minutes, and put it into the triple mold. Fix the triple mold on the vibration table and vibrate the material. Cover it with plastic wrap and place it in a constant temperature and humidity curing box for curing, with a humidity of 90% and a temperature of 30 degrees. The curing time is 7d, 14d, 28d, 56d, and 63d. Take out the samples respectively to observe whether there is "frosting" phenomenon, and test its strength. And test its strength.

[0091] As a control group of Example 5, Comparative Example 5 completed the following test:

[0092] Weigh 95g of water glass, add it to 300g of water, then add 7g of tetramethylacetyl octahydrogen and 0.5g of isooctyl phosphate, heat to 60°C, stir evenly to obtain a micellar solution, and cool to room temperature for use; add 25g of NaOH to the above micellar solution, stir for 30 minutes to obtain a uniform mixed solution, and leave it for 24 hours for use.

[0093] Weigh 1 kg of fly ash, pour it into the mixing pot of the cement mortar mixer, add the above mixed solution, stir slowly for 2 minutes, then stir quickly for 2 minutes, and put it into the triple mold. Fix the triple mold on the vibration table and vibrate the material. Cover it with plastic wrap and place it in a constant temperature and humidity curing box for curing, with a humidity of 90% and a temperature of 30 degrees. The curing time is 7d, 14d, 28d, 56d, and 63d. Take out the samples respectively to observe whether there is "frosting" phenomenon, and test its strength.

[0094] Table 9 Verification results of the "flour" phenomenon and compressive strength of the solidified material prepared in Example 5

[0095] Maintenance time / day Is there a "frosting" phenomenon? Compressive strength / MPa 7 none 4 14 none 15.7 28 none 23 56 none 31.2 63 none 35.6

[0096] Table 10 Verification results of the "flour" phenomenon and compressive strength of the solidified material prepared in Comparative Example 5

[0097] Maintenance time / day Is there a "frosting" phenomenon? Compressive strength / MPa 7 none 5.2 14 Appear 17 28 have 20.1 56 have 27.9 63 have 30.3

[0098] Embodiment 6:

[0099] In this Example 6, the organic base-activated geopolymer solidified material is prepared from fly ash, water glass (modulus 3.3), 2-naphthalenesulfonic acid, n-octanol, and isopropanolamine.

[0100] Weigh 97 g of water glass, add it to 350 g of water, then add 10 g of 2-naphthalenesulfonic acid and 1 g of n-octanol, heat to 60° C., stir evenly to obtain a micellar solution, and cool to room temperature for use; add 40 g of isopropanolamine to the above micellar solution, stir for 30 minutes to obtain a uniform mixed solution, and leave it for 24 hours for use.

[0101] According to the water-cement ratio of 0.30, weigh 1 kg of fly ash, pour it into the mixing pot of the cement mortar mixer, add the above mixed solution, stir slowly for 2 minutes, then stir quickly for 2 minutes, and put it into the triple mold. Fix the triple mold on the vibration table and vibrate the material. Cover it with plastic wrap and place it in a constant temperature and humidity curing box for curing, with a humidity of 90% and a temperature of 30 degrees. The curing time is 7d, 14d, 28d, 56d, and 63d. Take out the samples respectively to observe whether there is "frosting" phenomenon, and test its strength. And test its strength.

[0102] As a control group of Example 6, Comparative Example 6 completed the following test:

[0103] Weigh 97 g of water glass, add it to 350 g of water, then add 10 g of 2-naphthalenesulfonic acid and 1 g of n-octanol, heat to 60°C, stir evenly to obtain a micellar solution, and cool to room temperature for use; add 27 g of NaOH to the above micellar solution, stir for 30 minutes to obtain a uniform mixed solution, and leave it for 24 hours for use.

[0104] Weigh 1 kg of fly ash, pour it into the mixing pot of the cement mortar mixer, add the above mixed solution, stir slowly for 2 minutes, then stir quickly for 2 minutes, and put it into the triple mold. Fix the triple mold on the vibration table and vibrate the material. Cover it with plastic wrap and place it in a constant temperature and humidity curing box for curing, with a humidity of 90% and a temperature of 30 degrees. The curing time is 7d, 14d, 28d, 56d, and 63d. Take out the samples respectively to observe whether there is "frosting" phenomenon, and test its strength.

[0105] Table 11 Verification results of "flouriness" phenomenon and compressive strength of the solidified material prepared in Example 6

[0106] Maintenance time / day Is there a "frosting" phenomenon? Compressive strength / MPa 7 none 4.3 14 none 16.2 28 none 23.7 56 none 33.3 63 none 37.6

[0107] Table 12 Verification results of the "flour" phenomenon and compressive strength of the solidified material prepared in Comparative Example 6

[0108] Maintenance time / day Is there a "frosting" phenomenon? Compressive strength / MPa 7 none 5.1 14 Appear 16.7 28 have 21.3 56 have 26.9 63 have 31.2

[0109] Referring to the above-mentioned Examples 1 to 6 and Comparative Examples 1 to 6, in the embodiments of the present invention, the "frosting" phenomenon and compressive strength of the prepared organic base-activated geopolymer and the geopolymer solidified product prepared in the comparative example were verified, and it was found that after the addition of the organic base, the occurrence of the "frosting" phenomenon of the geopolymer was significantly solved, and the technical problem of the "frosting" phenomenon caused by the residual alkaline substance in the existing preparation method using (inorganic) alkaline solution as raw material was solved; at the same time, by adjusting the components, it was found that the weight percentage of the surfactant in the water was 1.71-2%, and the weight percentage of the defoamer in the water was 0.29-0.5%; when the weight percentage of the organic base in the water was 8.57-10%, the synergistic effect between the various components in the geopolymer was further enhanced, that is, Example 1 and Example 4 are the optimal embodiments, which not only have high compressive strength in a short time but also have the most stable compressive strength over a long period of time, that is, the compressive strength is significantly improved without frosting.

[0110] Based on the same inventive concept, an organic base-activated geopolymer solidified material prepared according to the above-mentioned method for preparing an organic base-activated geopolymer solidified material is provided in an embodiment of the present invention.

[0111] Based on the same inventive concept, an embodiment of the present invention provides an application of an organic alkali-activated geopolymer solidified material prepared according to the above-mentioned method for preparing an organic alkali-activated geopolymer solidified material in a construction project.

[0112] Based on the same inventive concept, an embodiment of the present invention provides an application of an organic alkali-activated geopolymer solidified material prepared according to the above-mentioned method for preparing an organic alkali-activated geopolymer solidified material in well completion or cementing.

[0113] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A method for preparing an organic base-activated geopolymer solidified material, characterized in that: include: Add water glass, surfactant and defoamer into water, heat and stir to obtain micellar solution, and then cool to room temperature for use; wherein the weight percentage of water glass to water is 10-40.33%, the weight percentage of surfactant to water is 1-7.14%, and the weight percentage of defoamer to water is 0.17-1%; Adding an organic base to the micellar solution and mixing them evenly to obtain a mixed solution; wherein the weight percentage of the organic base to the water is 1.83-11.67%; The fly ash is weighed according to the water-to-fly ash water-binder ratio of 0.3-0.35, poured into a mixing pot of a cement mortar mixer, and the mixed solution is poured into the mixing pot and stirred to prepare an organic alkali-activated geopolymer solidified product.

2. The method according to claim 1, characterized in that The weight percentage of the water glass to the water is 34.57-40.33%, the weight percentage of the surfactant to the water is 1-2%, the weight percentage of the defoamer to the water is 0.29-1%; the weight percentage of the organic base to the water is 3-11.42% or 11.67-20%.

3. The method according to claim 2, characterized in that The weight percentage of the surfactant to the water is 1.71-2%, the weight percentage of the defoamer to the water is 0.29-0.5%; and the weight percentage of the organic base to the water is 8.57-10%.

4. The method according to any one of claims 1 to 3, characterized in that: The surfactant is at least one of the following: lignin sulfonates, naphthalene, melamine, aminosulfonates, fatty acids, and polycarboxylates.

5. The method according to any one of claims 1 to 3, characterized in that: The defoaming agent is at least one of the following: oils and fats, alcohols, synthetic fatty acids and fatty acid esters, amides, phosphates, organosilicon compounds, halogenated organics, polyethers and polyether-type nonionic surfactants.

6. The method according to any one of claims 1 to 3, characterized in that: The organic base is an amine compound, including at least one of the following: aliphatic amines, alcohol amines, amides, alicyclic amines, aromatic amines, and naphthyl amines.

7. The method according to any one of claims 1 to 3, characterized in that: The modulus of the water glass is 3.

3.

8. An organic base-activated geopolymer solidified material prepared by the method for preparing an organic base-activated geopolymer solidified material according to any one of claims 1 to 7.

9. Use of an organic base-activated geopolymer solidified material prepared by the method for preparing an organic base-activated geopolymer solidified material according to any one of claims 1 to 7 in construction engineering.

10. Use of an organic base activated geopolymer solidified material prepared by the method for preparing an organic base activated geopolymer solidified material according to any one of claims 1 to 7 in well completion or cementing.

Citation Information

Patent Citations

  • Green geopolymeric cementitious material and preparation method thereof

    CN107382253A

  • Organic base excited geopolymer and preparation method thereof

    CN109734339A

  • All-solid-waste ecological cementing material

    CN110041015A

  • Alkali-activated fluidized bed fly ash geopolymer and preparation method thereof

    CN113321435A

  • Organic-inorganic composite alkali activator for alkali-activated cementing materials and preparation method of organic-inorganic composite alkali activator

    CN113929322A